Poor weight gain and its predictors among preterm neonates admitted at Muhimbili National Hospital in Dar-es-salaam, Tanzania: a prospective cohort study - Victoria Paul Ndembo; Helga Naburi; Rodrick Kisenge; Germana H. Leyna; Candida Moshiro (BMC, 2021)
Abstract Background Preterm delivery is among the major public health problems worldwide and the leading cause of morbidity and mortality among neonates. Postnatal poor weight gain, which can contribute to mortality, can be influenced by feeding practices, medical complications and quality of care that is provided to these high-risk neonates. This study aimed to investigate the proportion and predictors of poor weight gain among preterm neonates at Muhimbili National Hospital (MNH), from September 2018 to February 2019. Methods A hospital-based prospective cohort study involving preterm neonates with Gestation age (GA) < 37 weeks receiving care at MNH. Eligible preterm, were consecutively recruited at admission and followed up until discharge, death or end of neonatal period. Poor weight gain was defined as weight gain less than 15 g per kg per day. The risk factors associated with poor weight gain were evaluated. Predictors of poor weight gain were evaluated using a multivariate analysis. Results were considered statistically significant if P -value was < 0.05 and 95% confidence interval (CI) did not include 1. Results A total of 227 preterm neonates < 37 weeks GA, with male to female ratio of 1:1.2 were enrolled in the study. The overall proportion of preterm with poor weight gain was 197/227 (86.8%). Proportion of poor weight gain among the early and late preterm babies, were 100/113 (88.5%) and 97/114 (85.1%) respectively. Predictors of poor weight gain were low level of maternal education (AOR = 2.58; 95%Cl: 1.02-6.53), cup feeding as the initial method of feeding (AOR = 8.65; 95%Cl: 1.59-16.24) and delayed initiation of the first feed more than 48 h (AOR = 10.06; 95%Cl: 4.14-24.43). A previous history of preterm delivery was protective against poor weight gain (AOR = 0.33; 95% Cl: 0.11-0.79). Conclusion and recommendation Poor weight gain was a significant problem among preterm neonates receiving care at MNH. This can be addressed by emphasizing on early initiation of feed and tube feeding for neonates who are not able to breastfeed. Health education and counselling to mothers focusing on feeding practices as well as close supervision of feeding especially for mothers experiencing difficulties in feeding their preterm will potentially minimize risk of growth failure.